2022
DOI: 10.1097/iae.0000000000003401
|View full text |Cite
|
Sign up to set email alerts
|

Objective and Quantitative Estimation of the Optimal Timing for Epiretinal Membrane Surgery on the Basis of Metamorphopsia

Abstract: Purpose: To establish an objective and quantitative biomarker of metamorphopsia in epiretinal membranes (ERMs) and determine the optimal timing for ERM surgery.Methods: Retrospectively, 172 eyes with ERM were reviewed. Retinal folds because of tangential traction by ERM were visualized by en-face optical coherence tomography. The maximum depth of retinal folds (MDRF) within the parafovea was quantified. Metamorphopsia was quantified by M-CHARTS. The change in the distance between the retinal vessels after ERM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…It has been reported that the early manifestation of idiopathic ERM is metamorphopsia rather than visual acuity and that metamorphopsia has a significant impact on the patient's quality of life. 18 , 19 Recently, attempts have been made to determine the surgical indication for idiopathic ERM using MDRF as an objective quantitative parameter to evaluate metamorphopsia, 9 and similar surgical indication criteria should be established for ERM-FS and MPH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the early manifestation of idiopathic ERM is metamorphopsia rather than visual acuity and that metamorphopsia has a significant impact on the patient's quality of life. 18 , 19 Recently, attempts have been made to determine the surgical indication for idiopathic ERM using MDRF as an objective quantitative parameter to evaluate metamorphopsia, 9 and similar surgical indication criteria should be established for ERM-FS and MPH.…”
Section: Discussionmentioning
confidence: 99%
“…To quantitatively evaluate the strength of retinal traction, the MDRF was measured according to previous reports. 6 , 7 , 8 , 9 , 10 Briefly, the distance between the ILM surface and the surface on which the deepest retinal folds are seen was measured in the parafoveal area, i.e., a circle 3 mm in diameter centered on the fovea.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we focused on the depth of retinal folds caused by ERM and reported that this depth is an important objective and quantitative biomarker reflecting the tangential retinal traction force applied by ERM. 12 , 16 , 17 , 18 , 19 , 20 We further examined the relationship between the preoperative maximum depth of retinal folds within the parafovea (MDRF) and metamorphopsia and found that MDRF was significantly related to preoperative metamorphopsia. 16 , 19 , 21 In addition, utilizing the relationship between MDRF and metamorphopsia, we quantitatively identified the optimal timing of ERM surgery that does not compromise the patient’s quality of life.…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 19 , 21 In addition, utilizing the relationship between MDRF and metamorphopsia, we quantitatively identified the optimal timing of ERM surgery that does not compromise the patient’s quality of life. 19 …”
Section: Introductionmentioning
confidence: 99%